Developing a New Interval Type-2 Hesitant Fuzzy TOPSIS-Based Fuzzy Best-Worst Multicriteria Decision-Making Method for Competitive Pricing in Supply Chain - Farhad Salimian; Maryam Damiri; Mahyar Ramezankhani; Saeed Khakshouri Fariman (Journal of Mathematics)
Corporate social responsibility based on competitive supply chain pricing has been considered the most efficient strategy of a business globally. In an MCDM challenge, a competent supply chain pricing considerations solutions supplier considers multiple possibly competing for qualitative and quantitative criteria. This study presented a new extended decision-making and FBWM method based on type-2 fuzzy sets TOPSIS for ranking the corporate social responsibility criteria based on competitive supply chain pricing factors. The aim of the ranking is to learn how a company and its supply chain may accomplish joint-optimization of economic, environmental, and social performance by transparently and strategically integrating sustainability into business operations. To verify the efficacy of the suggested strategy, it is compared to a benchmarking model. IT2F VIKOR is the subject of this benchmarking model. The significance weights of the competitive supply chain pricing selection criterion are determined from BWM for both techniques. The results show that the most probable dimension of social responsibility in knowledge-based businesses in the oil sector, according to the research, is the environmental dimension in social responsibility, which may produce competitive supply chain pricing mechanisms based on profitability. Other findings revealed that the elements of competitive supply chain pricing factors in oil companies regarding social responsibility are ranked as follows: customer, product, and competitive supply chain pricing procedures. As a result, maintaining customer values is a major price element in establishing contacts, based on the company’s strategic connection with the economy and regional and worldwide partners.